Penerapan Nilai Pendidikan Karakter Pada Pembelajaran Biologi Materi Pencemaran Lingkungan Kelas X MAS Proyek UNIVA Medan - Supandi, Bunga; Akhyar, Sayed (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to describe the strategy for implementing character education values in biology learning on environmental pollution material in class X MAS UNIVA Medan Project, as well as identifying obstacles and impacts of the implementation. This study uses a qualitative method with a descriptive approach. Data collection techniques through observation, interviews, and documentation. The data analysis model used is the Miles and Huberman models. The subjects of the study consisted of 1 biology teacher and 15 students of class X MIA-1. The results of the study showed that the teacher's strategy was to implement the value of responsibility through collecting assignments and being responsible for bringing drinking bottles to reduce the use of plastic waste, the value of cooperation through group discussions and carrying out daily pickets so that the classroom environment becomes clean and comfortable and the value of caring for the environment through the habit of throwing garbage in its place and making crafts from plastic waste. The obstacles found included the lack of teacher understanding of character education, low student awareness of the environment, and the influence of bad habits from the environment outside the school. The behavior formed as a result of this implementation is an increase in student awareness of the importance of protecting the environment, the formation of responsible behavior, and the growth of cooperation between students in learning. The implications of this research are expected that students can be more active in participating in preserving the environment, for teachers it can provide new insights and strategies in integrating character values.